Sektor Pariwisata Indonesia di Tengah Pandemi Covid 19 - Betty Ayu Utami; Abdullah Kafabih (Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
In recent years, the contribution of the tourism sector has increased significantly, however at the beginning of 2020 the world was shaken by the presence of the Covid-19 virus outbreak. The President of Indonesia, Joko Widodo issued an instruction namely Large-Scale Social Restrictions (PSBB). Ban all countries or cities most affected by COVID-19 from entering their border areas. This research was conducted to see the condition of tourism in Indonesia in the midst of the Covid-19 pandemic and the steps taken by the government to restore the tourism sector using library research methods. The government through the Ministry of Tourism and Creative Economy (Kemenkarekraf) has taken several policy steps to improve the tourism sector and creative economy. The government is preparing another program, namely preparing a tourism grant fund program with a total budget of up to Rp. 3.3 trillion as the government's effort to maintain the economic sustainability of the tourism sector. Increasing exports and digitizing the marketing of creative economy products (Ekraf) are among the government's steps, so it is hoped that it can restore national tourism.